Science Skepticism, Science Education, and the Elephant in the Room - Dimitris Kilakos (National Dong Hwa University, 2025)
Science skepticism has become a prominent issue in public as well as in scholarly discourse. In turn, focusing on education and science literacy in attempts to deploy strategies aiming to deal with the issue of science skepticism seems to be a plausible option. However, interdisciplinary research points out that the relationship between educational attainment and science skepticism is arguably too complex to allow us to simply call for enhanced science literacy as a remedy. Furthermore, science skepticism is arguably a kind of Gordian knot of theoretical engagements with the scientific endeavor in its various aspects, since it gets even more perplexed in every step that metascientific studies attempt to make. The elephant in the room may become apparent and not negligible: it is the epistemological premises that inform our conception and image of science. This paper intends to suggest that there is a need to confer novel insights on the ongoing discussion on science skepticism with regard to both metascientific studies and science education by delving deeper into the development of the epistemological underpinning of stances regarding the scientific endeavor, addressing its social impact and their intertwining with science skepticism.